Determinants of the Stock Price Volatility In the Indonesian Manufacturing Sector - Handayani, Heny; Muharam, Harjum; Mawardi, Wisnu; Robiyanto, Robiyanto (International Research Journal of Business Studies, 2018)
This study aimed to analyze the influence of return on equity, debt to equity ratio, sales growth, firm size, cash ratio, and dividend payout ratio to stock price volatility companies listed on the Indonesia Stock Exchange in the period 2011-2015. The populations of this study are all manufacturing companies listed in Indonesia Stock Exchange (IDX) in the period 2011 to 2015. It obtained eight companies samples with technique purposive sampling method. The data analysis technique used is the regression model panel then be adjusted again by using GARCH (Generalized Autoregressive Conditional Heteroscedasticity). The results showed that the volatility of the stock price only affect without any effect ARCH-GARCH therein. Determining the best models of each prediction is based on estimated volatility GARCH (p, q). The determination of whether there is influence of the factors believed to be the determinants of stock price volatility was done by using panel data regression analysis. The results of panel data regression analysis showed that the company’s stock price volatility in the research samples can be explained by 4.84% by ROE, CR, DER, DPR, company size and sales growth while the remaining 95.16% explained by other variables outside the research. Only sales growth has significant positive effect on stock price volatility.